Covalent Modification of MoS2 with Poly(N‐vinylcarbazole) for Solid‐State Broadband Optical Limiters. Issue 13 (18th February 2016) - Cheng, Hongxia; Dong, Ningning; Bai, Ting; Song, Yi; Wang, Jun; Qin, Yuanhao; Zhang, Bin; Chen, Yu
Abstract: New soluble MoS2 nanosheets covalently functionalized with poly( N ‐vinylcarbazole) (MoS2 –PVK) were in situ synthesized for the first time. In contrast to MoS2 and MoS2 /PVK blends, both the solution of MoS2 –PVK in DMF and MoS2 –PVK/poly(methyl methacrylate) (PMMA) film show superior nonlinear optical and optical limiting responses. The MoS2 –PVK/PMMA film shows the largest nonlinear coefficients ( β eff ) of about 917 cm GW −1 at λ =532 nm (cf. 100.69 cm GW −1 for MoS2 /PMMA and 125.12 cm GW −1 for MoS2 /PVK/PMMA) and about 461 cm GW −1 at λ =1064 nm (cf. −48.92 cm GW −1 for MoS2 /PMMA and 147.56 cm GW −1 for MoS2 /PVK/PMMA). A larger optical limiting effect, with thresholds of about 0.3 GW cm −2 at λ =532 nm and about 0.5 GW cm −2 at λ =1064 nm, was also achieved from the MoS2 –PVK/PMMA film. These values are among the highest reported for MoS2 ‐based nonlinear optical materials. These results show that covalent functionalization of MoS2 with polymers is an effective way to improve nonlinear optical responses for efficient optical limiting devices. Abstract : Better than the sum of its parts : Soluble MoS2 nanosheets covalently functionalized with poly( N ‐vinylcarbazole) (MoS2 –PVK) were synthesized for the first time. In contrast to MoS2 and MoS2 /PVK blends, both a solution of MoS2 –PVK in DMF and MoS2 –PVK/poly(methyl methacrylate) (PMMA) film show superior nonlinear optical and optical limiting responses (see figure).